MORFOLOGI ABNORMALITAS SPERMATOZOA BABI LANDRACE DAN BABI DUROC DENGAN PEWARNAAN CARBOFUCHSIN - Ewaldus F. Patmawan; Cynthia D Gaina; Nancy D. F. K. Foeh (Jurnal Veteriner Nusantara, 2020)
This research was aimed to defined the morphology of boar’s sperm and using carbofuchsin staining. The semen sample were collected with technique glove hand method from three healty Landrace and Duroc boars belong to UPT pembibitan Ternak Babi Dinas Peternakan Provinsi NTT. Semen were stained using Carbofucsin staining technique, morphology observation was evaluated by microscop on 500 cells for each sample. From macroscopic and microscopic evaluation the result showed that the Landrace boar’s semen volume was308.33±23.63 ml, the pH was 7,4 and the sperm concentration was 230±20x106 cell/mL. Macroscopic and microscopic evaluation the result showed that the Duroc boar’s semen volume was 213.33±41.63 ml, the pH was 7,4 and the sperm concentration was 455±198.30x106 cell/mL. The result of morphology observation in Landrace and Duroc boars showed that the normal sperm was 95.91±1.14% and94.02±2.76%. Abnormal sperm in Landrace and Duroc was4.13±1.11% dan 5.97±2.76%. The abnormality of theLandrace and Duroc sperm consist of narrow (0.07% and0,26%), acrosome defect (0,27% and 0,1%), pear shapered (0,49% and 0.18%), double head (0,07% and 0,04%), variable size (0.11% and 0,12%), lose abnormal head (0.06% and 0,32%) and tail abnormalities (1,72% dan 4,36%). Based on the evaluation of semen and morphological observations in this research can be concluded that the boars semen used in good conditio